ANALISIS CERPEN “BADAI YANG REDA” KARYA FAUZIA A: PERSPEKTIF SOSIAL DAN PSIKOLOGIS DALAM PENCARIAN JATI DIRI - Listanto, Firgiawan; Arfiah, Siti; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study uses a qualitative-descriptive method with a literary approach, especially a sociological and psychological approach to literature. This method was chosen because it is appropriate for revealing the meaning contained in literary texts in depth, especially those related to social dynamics and the psychological conditions of the characters in the short story. This approach also allows researchers to analyze how social structures and environmental pressures influence the main character's inner journey in finding their identity. The short story